Densification and mechanical properties of electroconductive Si3N4 -based composites prepared by spark plasma sintering - Norhayati Ahmad; Hidekazu Sueyoshi (Universiti Kebangsaan Malaysia, 2012)
Si3N4-TiN composites were prepared by conventional powder processing (SPS1) and in-situ reaction sintering (SPS2). Rapid densification of SPS was achieved for sample SPS1 and SPS2 within a few minutes at low temperature. Sample SPS1 sintered at 1550ºC showed rapid transformation of α to β Si3N4 while for sample SPS2 sintered at 1350ºC, a significant degree of α to β Si3N4 transformation was achieved. Homogeneous distribution of equiaxed TiN grains in matrix Si3N4 resulting in high hardness (21.7 GPa) and bending strength (621 MPa) for sample SPS1 sintered at 1550ºC. Elongated TiN grains as the reinforcement of Si3N4 matrix composites was found to increase the toughness (8.39 MPa m1/2) of sample SPS2 sintered at 1350ºC. The composites prepared by SPS2 sintered at 1250-1350ºC had low electrical resistivity and could be machined by electrical discharge machining (EDM).